Impact of Power Play Overs on the Outcome of Twenty20 Cricket Match - Dibyojyoti Bhattacharjee; Manish Pandey; Hemanta Saikia; Unni Krishnan Radhakrishnan (The Society of Aging and Physical Activity (SAPA), 2016)
This study attempts to find if better performance in power play leads a team to victory in a Twenty20 match. Based on the methodology devised to do so, the study tries to measure the performance of both the teams during power play overs in terms of batting and bowling. The developed measure is called ‘Prod’ which is a product of the difference of batting and bowling performance of the teams during power play overs. The team with better performance in both the skills during power play is expected to win the match. But it would be difficult to predict the outcome of a match if the performance of a team is better in bowling and worse in batting and vice-versa. A total of 261 matches from different seasons of Indian Premier League (IPL) are considered for the study. The outcomes of 220 matches are predicted based on the performance of two teams in power play out of which 153 of them were correctly predicted. Remaining 41 matches could not be predicted as it is not clear which team performed better during power play. Thus, out of the matches where the dominance of a team was clear in the power play, 70 percent cases that team ultimately won the match in Twenty20 cricket.